Clinical and epidemiological characteristics of patients with COVID-19 at a high-altitude hospital - Díaz-Lazo, Aníbal (2021)
Objective: To determine the clinical and epidemiological characteristics of patients with COVID-19 at a high-altitude hospital. Materials and methods: An observational, cross-sectional and analytical study carried out at the Hospital Daniel Alcides Carrión in Huancayo, Peru, located at 3,250 m a.s.l. The population consisted of 2,248 people. COVID-19 was diagnosed through serology testing and/or reverse transcription polymerase chain reaction (RT-PCR) testing. Data were recorded in a questionnaire. For the statistical analysis, the X2 test, Student’s t-test, and bivariate and multivariate logistic regression analyses were used. A p value < 0.05 was considered statistically significant. Results: The study population with a diagnosis of COVID-19 accounted for 760 patients (100 %), most of whom were males (474 individuals; 62.36 %). The average age was 49 years (range: 15 to 95). Most cases were found in the age group of 40 to 59 years (38.82 %), particularly among housewives (21.44 %) and traders (19.21 %). The most common COVID-19 symptoms were cough (70.26 %), malaise (57.63 %), respiratory distress (48.81 %), fever (48.15 %) and sore throat (44.21 %). The most frequent comorbidities were obesity (4.47 %), diabetes mellitus (2.76 %) and arterial hypertension (1.31 %). Fifty-one point seven one percent (51.71 %) of the patients required hospitalization and the mortality rate was 14.21 %. The risk factors for mortality were age 60 years or older (OR = 4.74; 95 % CI: 2.94 - 7.65; p = 0.000), respiratory distress (OR = 2.38; 95 % CI: 1.42 - 3.99; p = 0.001) and use of mechanical ventilation (OR = 8.75; 95 % CI: 4.45 - 17.22; p = 0.000). Conclusions: COVID-19 most frequently affects the adult population. Cough and malaise were the most common symptoms, while older age, dyspnea and use of mechanical ventilation were associated with a higher risk of mortality.